Principal's Leadership Style in Improving the Quality of Teachers' Work at Al-Fauzan Private MTs Labuhanbatu for the 2024–2025 Academic Year - Azmi Nasution; Syahrul Budiman; Betti Megawati (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to determine the leadership style of the principal in improving the quality of teacher work at MTs Swasta Al-Fauzan Labuhanbatu in the 2024-2025 academic year. The focus of the study includes the form of leadership style applied, supporting and inhibiting factors, and the impact of this leadership on teacher performance. This research uses a qualitative descriptive method, relying on interviews, observations, and the examination of documentation for data collection purposes. The data analysis technique used is a qualitative descriptive analysis technique, which is carried out by reviewing the existing data, then reducing data, presenting data, and drawing conclusions. The results of the study show that the principal applies a transformational and participatory leadership style, which is characterized by the ability to motivate teachers, create a conducive work environment, and involve teachers in decision making. Supporting factors include a harmonious relationship between the principal and teachers, as well as support from education personnel. The inhibiting factors include limited facilities and lack of professional training for teachers at the MTs. So it was found that the right leadership style of the principal greatly influences the improvement of the quality of teacher work. Therefore, communicative, inspiring leadership is needed, and is able to empower all elements of the school.